Proximate and Mineral Composition of Fish Bone Powder of Siganus lineatus Collected from Waters Around Jaffna Peninsula, Sri Lanka - Thayalini, T.; Uventhikka, S.; Sivashanthini, K.; Jasotha, P.; Velauthamurty, K. (Uva Wellassa University, 2023)
Siganus lineatus is one of the marine reef fish which found in marine and brackish water environment. The family Siganidae is nutritionally and economically important in Sri Lanka. Thus the knowledge on their chemical composition could help to be used as an ingredient of traditional medicine to cure osteoporosis in the future. The current study was aimed to produce Siganus lineatus fishbone flour and analyze the selected nutritional composition. From December 2019 to February 2020 Siganus lineatus were collected from the Jaffna coasts. Fishbones were boiled into a water medium. The treated fish bones were ground for easy handling. Proximate composition of lipid, moisture, protein, ash and mineral composition of calcium, phosphorus, potassium, and sodium were determined. AOAC and AOCS standards were used in the proximate analysis. Mineral compositions were determined by using a Digital Flame Photometer for Calcium (Ca), Potassium (K) and Sodium (Na) and by Multiparameter Photometer for phosphorus (P). The ash, protein, moisture, and lipid contents were 50.74±0.65%, 22.07±0.29%, 6.29±0.35% and 3.50±0.16% in fishbone of Siganus lineatus respectively. The mineral composition Ca, P, K, and Na were 12.5%, 7.66%. 0.42% and 0.36% respectively and the ratio of calcium: phosphorus is 2:1. In this study, the water extraction method showed higher ash content so this method could be used to extract the mineral content from fishbone. Results demonstrated that extracted fish bone powder was nutritious and can contribute importantly to human health requirements of calcium-deficient disease in future.
Keywords: Calcium deficient disease; Digital Flame Photometer; Fishbone powder; Multiparameter Photometer; Siganidae; Siganus lineatus